Desenvolvimento de ligas amorfas e nanocristalinas do sistema Fe-Cr-Ni-B e suas propriedades de corrosão - Berger, José Eduardo (2019)
Fe-Cr-Ni-B system alloys with partially amorphous structures can ensure a very attractive combination of mechanical and electrochemical properties, far superior to conventional materials. It can be used, for example, in the form of metallic coatings in parts or equipment, in which, wear mechanisms coupled with the high aggressiveness of the media are present, as is the case in the petrochemical sectors. The success of the elaboration and projection of an alloy that can provide specific characteristics and properties depends on the degree of knowledge and familiarity with the peculiarities of each composition of the system, from the formation of possible phases and structures to the consequences and limitations of the microstructure in its specific use. In this way, the present work aims to perform a mapping of the characteristics, trends and behavior of the Fe-Cr-Ni-B system alloys. Based on thermodynamic simulations, a series of alloys was elaborated, covering a large range of compositions of potential interest, in order to register patterns and trends of formation of crystals and structures, correlating them with the final properties of the alloy. The alloys were produced in the form of ribbons in melt-spinning equipment. Vacuum heat treatments were used for partial and total crystallization of amorphous alloys, as well as for the evaluation of structural alterations of crystalline phases. The study methods used were: Thermodynamic simulation in Thermo-Calc® software, using the TCFe7 database, X-ray diffraction (XRD), differential scanning calorimetry (DSC), transmission electron microscopy and automatic phase mapping (MET/ ASTAR) and electrochemical tests to obtain the polarization curves in high salt concentration media. At the end of the work a series of peculiarities of the Fe-Cr-Ni-B system could be registered, helping in a valuable way the understanding of the system. Revealing that, excellent corrosion resistance properties can be obtained by partially amorphous alloys containing both the superduplex stainless structure and boride particles.